Effect of post-traumatic stress disorder on school achievement among secondary school students in Baghdad, Iraq - Al-Hemiary, Nesif J.; Hashim, Mushtaq T.; Al-Shawi, Ameel F.; Al-Diwan, Jawad K. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Iraqi people were exposed to mass disasters for long periods of time. Posttraumatic stress disorder (PTSD) may be of particular interest following a mass disaster. Evidence of poor school outcomes among adolescents affected by violence has been reported. Objectives: To study the effect of PTSD on school achievement among secondary school children in Baghdad, Iraq. Materials and methods: A total of 240 secondary school students from 4 secondary schools (2 for boys and 2 for girls) from Baghdad city were included. Multistage random sampling was carried out. Each student was interviewed and a questionnaire (consisted of demographic information, Harvard Trauma Questionnaire, and academic failure) was filled. Academic failure was indicated by poor school achievement. Results: Students with PTSD were 37.1%. No significant association was found between age, sex and PTSD.Of those with PTSD, 86.5% had bad school achievement. Conclusion: high rate of PTSD was reported among secondary school students, and PTSD had a negative impact on their school achievement